Assessment of COVID 19 Post-Vaccine Side Effects among People Attending Al- Sheikh Zayed Hospital in Baghdad - Aqeel Hasan; Sabeha Hummadi; Rawaa Sadkhan; Moatz Ali (Kufa Journal for Nursing Sciences)
Background: Vaccines in general are save lives of population, it is providing strong protection against serious illness and death. COVID-19 vaccine could decrease mortality rate caused by infection.  WHO reports that unvaccinated people have at least 10 times higher risk of death from COVID-19 than somebody who has been vaccinated.